Ousting South Africa: Olympic clashes of 1968 - Sikes, Michelle (University of the Free State, 2018)
South Africa modified its sport policy, though not its national policy of apartheid, prior to the 1968 Mexico City Olympic Games. Black and white South African athletes would compete as one team at the Olympics for the first time. This reversal of its previous allwhite policy persuaded the majority of IOC members to accept South Africa’s participation at the 1968 Olympics. African nations were the first to withdraw in protest. Taking this stand, despite South Africa’s concessions, they sought nothing less than the end of apartheid itself. Recognising that a detailed historical interrogation can shed light on the struggles, politics, limitations, and achievements of social justice in and through sport, this article demonstrates when and how these different visions of social justice emerged, gained traction, and were resisted when it came to apartheid South Africa.
Keywords: Acta Academica; Sport policy; Olympics; Apartheid; 1968 Mexico City Olympic Games